Analisis Kualitatif Pengaruh Pemasaran melalui TikTok terhadap Brand Engagement dalam Industri Fashion: Tinjauan Literatur - Bima Sakti, Danuarta; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
The rise of social media platforms such as TikTok has significantly transformed digital marketing strategies, especially in the visually-driven fashion industry. TikTok’s short-form, interactive video format offers brands an opportunity to enhance consumer engagement through creative content and user participation. This study aims to analyze the impact of TikTok marketing on brand engagement within the fashion sector. A qualitative approach was used by analyzing various relevant literature sources, including academic articles and research reports. Findings indicate that interactive content and influencer endorsements significantly increase consumer loyalty and trust in fashion brands. However, this study's limitations include reliance on existing literature without direct empirical data and the ever-evolving nature of TikTok trends. The results provide valuable insights for developing digital marketing strategies on the TikTok platform.